Understanding the small world: an insight into the application of transmission electron microscopy in characterizing epitaxial layers - Zul Azhar, Zahid Jamal, Prof. Dr. (Penerbit Universiti Malaysia Perlis, 2010)
Transmission electron microscopy (TEM) is an unrivalled technique for observing, characterizing and analyzing almost any type of materials. In physical science, the first observations of defects (i.e. dislocations) by TEM were published in the 1950s. Since then the technique has been developed into an indispensable tool for materials scientists, not only for the characterization of extended defect structures of materials, but also for the understanding of the mechanisms that control their properties. In this Professorial Lecture publication, a snapshot on the tremendous power and versatility of this technique is discussed. In addition to the basics and fundamentals of TEM, related research works on the characterization of defects in semiconducting epitaxial layers that I had pioneered and contributed to, namely on the development of large‐area TEM specimen preparation techniques, the characterization of the diamond‐shape defects, and the study of dopant diffusivity via TEM, are presented.